2022
DOI: 10.1002/hbm.26115
|View full text |Cite
|
Sign up to set email alerts
|

Information‐based multivariate decoding reveals imprecise neural encoding in children with attention deficit hyperactivity disorder during visual selective attention

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder in school‐age children. Attentional orientation is a potential clinical diagnostic marker to aid in the early diagnosis of ADHD. However, the underlying pathophysiological substrates of impaired attentional orienting in childhood ADHD remain unclear. Electroencephalography (EEG) was measured in 135 school‐age children (70 with childhood ADHD and 65 matched typically developing children) to directly investigate target locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Second, and most relevant to the current study, recent evidence has demonstrated a greater efficacy of the MVPA of EEG data in identifying hidden neural dynamics exhibited by individuals with neurodevelopmental (Williams Syndrome: Farran et al, 2020; ADHD: Li et al, 2023) and psychiatric (Schizophrenia: Bae et al, 2020) disorders. Indeed, for populations in which the observed behavior is the result of an alternative developmental pathway, potentially supported by distinct neural mechanisms, a multivariate approach may provide a more explanatory understanding of their sensory and cognitive profile.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, and most relevant to the current study, recent evidence has demonstrated a greater efficacy of the MVPA of EEG data in identifying hidden neural dynamics exhibited by individuals with neurodevelopmental (Williams Syndrome: Farran et al, 2020; ADHD: Li et al, 2023) and psychiatric (Schizophrenia: Bae et al, 2020) disorders. Indeed, for populations in which the observed behavior is the result of an alternative developmental pathway, potentially supported by distinct neural mechanisms, a multivariate approach may provide a more explanatory understanding of their sensory and cognitive profile.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, similarly to some recent studies (Bae et al, 2020;Farran et al, 2020;Li et al, 2023;Mares et al, 2020), we analyzed different key decoding parameters that allow a deeper investigation of the neural activation profiles differences associated with the discrimination of the experimental classes between ASD and TD groups. These parameters, which were tested using independent sample ttests, are: (i) decoding onset, that is, the first timepoint at which decoding becomes significant; (ii) decoding sustainability, that is, the percentage of significant timepoints decoded over time; (iii) decoding peak, that is, the highest decoding accuracy value (AUC); (iv) decoding peak latency, that is, the timepoint at which accuracy (AUC) is highest.…”
Section: Mvpa Analysisdiagonal Decodingmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed language development in typically developing children. So all participants exhibited IQ ≥80 according to the Wechsler Intelligence Scale for Chinese Children-Revised (WISCC-R) ( Wang et al, 2021 ; Li et al, 2023 ). Children diagnosed by a specialist with attention deficit hyperactivity disorder, autism, psychological disorders, intellectual disability, and a history of psychiatric disorders or brain damage were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%